Corrigendum to Patterns of diversification amongst tropical regions compared: A case study in Sapotaceae (2015)
A Corrigendum on Patterns of diversification amongst tropical regions compared: a case study in Sapotaceae by Armstrong, K. E., Stone, G. N., Nicholls, J. A., Valderrama, E., Anderberg, A. A., Smedmark, J., et al. (2014). Front. Genet. 5:362. doi: 10.3389/fgene.2014.00362